2017
DOI: 10.1097/ruq.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

Radiologist and Sonographer Interpretation Discrepancies for Biliary Sonographic Findings

Abstract: The aim of this study was to determine the discrepancy rate that exists between the preliminary interpretation by sonographers and the subsequent final radiology interpretation for biliary sonographic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
0
13
2
Order By: Relevance
“…The high accuracy of sonographers’ diagnostic opinion has been documented in numerous studies across all subspecialties with sonographers often demonstrating comparable standard of diagnostic performance to that of radiologists . This raises important questions about the level of oversight that sonographers require by imaging specialists such as radiologists or other sonologists and the required staffing levels and departmental structures.…”
Section: Introductionmentioning
confidence: 99%
“…The high accuracy of sonographers’ diagnostic opinion has been documented in numerous studies across all subspecialties with sonographers often demonstrating comparable standard of diagnostic performance to that of radiologists . This raises important questions about the level of oversight that sonographers require by imaging specialists such as radiologists or other sonologists and the required staffing levels and departmental structures.…”
Section: Introductionmentioning
confidence: 99%
“…18 Currently, there are no articles in the literature which compare sonographer's opinions and radiologists' reports regarding US LI-RADS cat and vis scores. In a broader search, a retrospective analysis of biliary sonographic findings of 400 scans by Dawkins et al 19 found a discrepancy rate of 15.5% between the preliminary interpretation by sonographers and the final radiologist's report.…”
Section: Discussionmentioning
confidence: 99%
“…Sonographers are highly accurate diagnosticians whose diagnostic performance in US has been shown to be on a par with that of radiologists in a number of studies. [23][24][25][26][27][28][29][30] There is therefore no reason to suspect that under the additional pressure of a pandemic, the sonographer's diagnostic performance would somehow become compromised.…”
Section: Discussionmentioning
confidence: 99%